Functional and antigenic constraints on the Nipah virus fusion protein - Brendan B. Larsen; Sheri Harari; Risako Gen; Cameron Stewart; David Veesler; Jesse D. Bloom (Proceedings of the National Academy of Sciences, 2026)
Nipah virus is a highly pathogenic virus in the family Paramyxoviridae that utilizes two distinct surface glycoproteins to infect cells. The receptor-binding protein (RBP) binds host receptors whereas the fusion protein (F) merges viral and host membranes. Here, we use nonreplicative pseudoviruses to safely measure the effects of all F single amino acid residue mutations on its cell entry function and neutralization by monoclonal antibodies. We compare mutational tolerance in F with previous experimental measurements for RBP and show that F is much more functionally constrained than the RBP. We also identify mutationally intolerant sites on the F trimer surface and core that are critical for proper function, and describe mutations that are candidates for stabilizing F in the prefusion conformation for vaccine design. We quantify how F mutations affect neutralization by six monoclonal antibodies, and show that the magnitude of mutational effects on neutralization varies among antibodies. Our measurements of mutational effects on Nipah virus F predict the ability of the antibodies to neutralize the related Hendra virus. Overall, our work defines the functional and antigenic constraints on the F protein from an important zoonotic virus.